Knowledge, attitude and practice of Iranian people regarding the use of antibiotics and its resistance - nooshin mohammadhosseini; farshad hashemian; mitra amini (Islamic Azad University, 2018)
Objective and Background The aim of this study was so assess the knowledge and attitude of the people in Iran regarding the antibacterial resistance caused by antibiotics. Introduction increasing concern toward antibiotic resistance led to many researches on the causes of this issue. The public awareness plays a critical role, according to the studies. Another important factor is the attitude of the people regarding the antibiotic use and the effect of their behavior on its resistance. The practice of each individual patient may contribute to the antibiotic resistance and major health problems and increased rate of death. materials and method A questionnaire based survey was carried out among the female population of 1000 in Tehran, Iran. An intervention course was carried out, training the volunteers. After the completion of the training course, the volunteers had to take another test to asses the effect of the training on the knowledge, attitude and practice of people regarding the antibiotic use. results and discussion Before the course, people considered antibiotic as safe drugs, therefore taking them without prescription and the malpractice was evident from the incomplete course of treatment. There was a significant difference indicating the effect of the course on the public awareness and their attitude which may lead to better practice regarding antibiotic use. There may be other contributing factors to the malpractice such as financial status and experience of no significant toxicity of the drugs, making them an optimum prevention or treatment option, according to the public. This intervention was successful regrading the attitude of the people, but long term studies are required to assess them in practice.